2014
DOI: 10.1159/000357799
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction as a Complication in Acute Stroke: Results from the Austrian Stroke Unit Registry

Abstract: Background: Patients with transient ischemic attack (TIA) and stroke have an increased risk for subsequent cardiac events including myocardial infarction (MI), which might be associated with a worse clinical outcome. Rapid identification of stroke patients at higher risk for MI might foster intensified cardiac monitoring or certain therapeutic strategies. However, information regarding acute MI as a complication of stroke in the very acute phase is limited. Moreover, there are no systematic data on the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…In addition, the more intensive lowering of blood pressure recommended for AMI may be harmful in patients with acute ischemic stroke, with current guidelines only recommending treatment for specific individuals receiving thrombolytic therapy or with other acute organ injury or marked blood pressure elevations [7] . Furthermore, clinically relevant AMI after stroke (as defined by standard criteria and clinical judgment) occurs substantially less often than troponin elevation alone, as noted in a recent analysis from a national registry [36] . This latter finding may explain why many standard AMI therapies are not associated with risk reduction in troponin-positive stroke patients, with troponin functioning more as a prognostic marker than a diagnostic test for AMI in these individuals.…”
Section: Prior Troponin Studiesmentioning
confidence: 98%
“…In addition, the more intensive lowering of blood pressure recommended for AMI may be harmful in patients with acute ischemic stroke, with current guidelines only recommending treatment for specific individuals receiving thrombolytic therapy or with other acute organ injury or marked blood pressure elevations [7] . Furthermore, clinically relevant AMI after stroke (as defined by standard criteria and clinical judgment) occurs substantially less often than troponin elevation alone, as noted in a recent analysis from a national registry [36] . This latter finding may explain why many standard AMI therapies are not associated with risk reduction in troponin-positive stroke patients, with troponin functioning more as a prognostic marker than a diagnostic test for AMI in these individuals.…”
Section: Prior Troponin Studiesmentioning
confidence: 98%
“…Recent data from the prospective Austrian Stroke Unit Registry, which included 4984 ICH patients, found that 0.3% of patients had an MI over a median duration of 3 days. 175 These patients not only experienced higher inhospital mortality but also had greater complications, including pneumonia and progressive stroke. History of prior MI and severity of deficits on admission are associated with the occurrence of MI.…”
mentioning
confidence: 99%
“…Since data were obtained by cross-linking the hospital database with NHS primary care data, all incident MI events occurring during the follow-up period were recorded unless they occurred outside the United Kingdom and were not recorded within the NHS primary care database.Characteristic data and relevant covariates were selected based on existing literature[10][11][12] and clinical judgement. We highlight a range of potential areas to focus preventative efforts.ischaemic stroke, mortality, myocardial infarction, risk factors of Disease (ICD-10), based on patient history, ECG findings, and cardiac troponin levels (ICD I21; ST elevation [STEMI] and non-ST elevation [NSTEMI] myocardial infarction).…”
mentioning
confidence: 99%